Both incidence and prevalence of ischaemic heart disease are declining in parallel: a national data-linkage study in New Zealand (ANZACS-QI 52). (17th December 2020) - Grey, Corina; Jackson, Rod; Wells, Sue; Wu, Billy; Pujades-Rodriguez, Mar; Schmidt, Morten; Selak, Vanessa; Kerr, Andrew J
Abstract: Aims: To examine trends in ischaemic heart disease (IHD) incidence and prevalence in New Zealand from 2005 to 2016, using comprehensive linked national hospitalization and mortality data as proxy measures of all significant events. Methods and results: Incident and prevalent cases of IHD in people aged ≥25 years were identified using individual patient-linkage of routinely collected ICD-10-coded hospitalization and mortality data. Incidence rates and prevalence proportions were calculated by sex and age group and then age-standardized to the 2016 New Zealand population. Ischaemic heart disease incidence and prevalence declined in men and women in all age groups. The average annual rate of decline in age-standardized IHD incidence was 3.3% for women and 2.7% for men, and the rate of decline in age-standardized IHD prevalence was 3.2% for women and 2.2% for men. Despite a 17% increase in the New Zealand population aged 25 years and over during the study period, the total number of people living with IHD also decreased, particularly in those aged 65 years and older. Conclusion: In contrast to observations from other countries, where IHD incidence but not IHD prevalence has been falling, declining IHD incidence in New Zealand in recent decades is now mirrored by declining IHD prevalence.